The spread of deposit insurance and the global rise in bank asset risk since the 1970s - Calomiris, Charles W.; Chen, Sophia (Journal of Financial Intermediation, 2022)
We construct a new measure of deposit insurance generosity for many countries, empirically model the exogenous international influences on the adoption and generosity of deposit insurance and use a novel econometric method to explore the causal chain from the expansion of deposit insurance generosity to increased overall lending, increased lending to households, increased banking system leverage, and more severe and frequent banking crises. Greater deposit insurance generosity robustly produces greater overall lending relative to bank assets and more lending to households relative to both bank assets and GDP, and results in higher banking system leverage. Our estimates, however, are not conclusive regarding whether greater deposit insurance generosity resulted in greater total loans relative to GDP or in more frequent or severe banking crises.